Sediment Remediation for Ecosystem in Eutrophic Lakes - Y. Amano; K. Taki; K. Murakami; T. Ishii; H. Matsushima (The Scientific World Journal)
The remediation method — namely, a hybrid system combined with DAF and CRM — is studied in this paper for the size reduction of aqua-ecological circulation and for the elution control in lakes. Results show that two effects on water quality purification, the sediment washout effect and the elution control effect, can be induced by this system, and the biota inhabiting the lake is therefore shifted into an oligotrophic aspect, from blue algae to green algae and/or diatoms.